2020
DOI: 10.15252/embj.2020105696
|View full text |Cite
|
Sign up to set email alerts
|

MiT/ TFE factors control ER ‐phagy via transcriptional regulation of FAM 134B

Abstract: Lysosomal degradation of the endoplasmic reticulum (ER) via autophagy (ER‐phagy) is emerging as a critical regulator of cell homeostasis and function. The recent identification of ER‐phagy receptors has shed light on the molecular mechanisms underlining this process. However, the signaling pathways regulating ER‐phagy in response to cellular needs are still largely unknown. We found that the nutrient responsive transcription factors TFEB and TFE3—master regulators of lysosomal biogenesis and autophagy—control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(30 citation statements)
references
References 54 publications
2
28
0
Order By: Relevance
“…ER-phagy could be similar to the regulation of peroxisome number, the balance between peroxisome biogenesis and pexophagy, and to the control of mitochondrial homeostasis (Dunn et al, 2005;Kundu and Thompson, 2005). TFEB and TFE3, nutrient responsive transcription factors, increase the expression of ERphagy receptor reticulophagy regulator 1 (RETREG1)/FAM134B to induce ER-phagy (Cinque et al, 2020). C53, a cytosolic protein, is involved in the formation of autophagosome under ER stress condition (Stephani et al, 2020).…”
Section: Er-phagymentioning
confidence: 99%
“…ER-phagy could be similar to the regulation of peroxisome number, the balance between peroxisome biogenesis and pexophagy, and to the control of mitochondrial homeostasis (Dunn et al, 2005;Kundu and Thompson, 2005). TFEB and TFE3, nutrient responsive transcription factors, increase the expression of ERphagy receptor reticulophagy regulator 1 (RETREG1)/FAM134B to induce ER-phagy (Cinque et al, 2020). C53, a cytosolic protein, is involved in the formation of autophagosome under ER stress condition (Stephani et al, 2020).…”
Section: Er-phagymentioning
confidence: 99%
“…The function of ER-phagy in cancer is unclear. Carmine settembre et al reported that MiT/TFE factors can trigger ER-phagy by directly transcriptional regulation of FAM134B 39 . We found that E-Syt1 is downstream of TFE3 and acted upstream of FAM134B during ER-phagy.…”
Section: Discussionmentioning
confidence: 99%
“…Signaling pathways of IRE1α, PERK, ATF6 and Ca2 + are necessary for the activation of ER stressmediated autophagy [46][47][48] , while the receptor-mediated ER-phagy that degrades the ER requires FAM134B [49][50][51] . FAM134B is an ER-resident receptor which contains a conserved putative LC3-interacting region (LIR motif).…”
Section: Discussionmentioning
confidence: 99%